PENGGUNAAN MEDIA KONKRET UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV PADA MATA PELAJARAN MATEMATIKA DI SDN 47 PEKANBARU - Siti Rahma Hasibuan; Annisa Fitri Septi; Hadinurdina; Zetra Hainul Putra; Beni Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics is one of the subjects that is difficult for students to understand. This makes teachers use many ways to help students understand the material presented, one of which is the use of media. Media itself is one of the ways used by teachers in delivering material to achieve learning objectives. Students who are involved in learning with concrete media show an increase in conceptual understanding, learning motivation, and active involvement in the learning process. The implication of this study is the importance of considering the use of concrete media as a learning strategy that can improve the effectiveness of mathematics teaching at the elementary school level. This study aims to improve mathematics learning outcomes by using concrete media in grade IV students of SDN 47 Pekanbaru. Classroom Action Research in cycle I and cycle II. The results of cycle I 2.6 and cycle II 3.4 are good, student activity in cycle I 2.4 and cycle II 3.6 are in the very good category and the learning results of cycle I 57 are in the sufficient category and cycle II 79 are in the good category. Cycle I 25% and cycle II 75% are in the good category. Based on these results, concrete media can improve student learning outcomes.